Impermeable concrete and preparation method thereof
By using components such as zeolite, aqueous acrylic emulsion and composite fibers in concrete, the problem of insufficient anti-seepage performance of existing concrete is solved, and efficient self-condensation and self-conservation effects are achieved, which significantly improves the waterproof performance and service life of the building.
Patent Information
- Application Number
- CN202411970404.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
In the construction environment and use process, existing concrete is difficult to meet the performance requirements of self-condensation, self-maintenance, low hydration heat, low shrinkage, high plastic protection and high durability. At the same time, its impermeability resistance is insufficient, resulting in the problem of difficult to detect large-area leakage points in the underground space waterproof design.
The anti-seepage concrete formula including cement, sand material, aggregate, microbeads, fly ash, zeolite, expansion agent, water reducing agent, aqueous acrylic emulsion and composite fiber is adopted. Through the thickening of zeolite and the action of moisture carrier, the secondary hydration time is extended, the system alkali content is reduced, and the self-compression and anti-seepage properties are improved. At the same time, the aqueous acrylic emulsion and composite fiber are used to improve the wetting, flowability and crack resistance of concrete respectively.
The self-containing, self-conservation and high permeability of concrete are achieved, structural cracking and water resource consumption are reduced, and the waterproof performance and service life of the building are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, and in particular to an anti-seepage concrete and a preparation method thereof. Background Art
[0002] With the progress of urbanization, the development of underground space is becoming more and more important in order to save land resources. The utilization of underground space in construction projects can alleviate the tension of land resources. Therefore, whether the underground space can meet the use function is particularly important for the waterproofing of the underground space. At this stage, the main structure of the underground space is constructed by integral casting of concrete. The quality of the concrete used determines the overall performance and service life of the structure. Therefore, high-performance concrete should not only meet the compressive requirements, but also meet the requirements of self-compacting, self-maintenance, low hydration heat, low shrinkage, high plasticity and high durability according to the changes in the construction environment and conditions and the requirements of different structural objects to meet the concrete's own anti-permeability performance.
[0003] Therefore, during the implementation of the project, waterproof design is often adopted in underground spaces, mainly using waterproof membranes or waterproof coatings to waterproof buildings. However, once the waterproof surface of this type of waterproofing is damaged, it is difficult to find the leakage points of a large area, which will cause a lot of cost investment for future maintenance. Summary of the invention
[0004] The invention provides an impermeable concrete and a preparation method thereof, which can enhance the impermeability of the concrete itself.
[0005] An embodiment of the present invention provides an impermeable concrete, comprising the following components in parts by weight: 18-26 parts of cement, 7-13 parts of sand, 8-20 parts of aggregate, 5-9 parts of microspheres, 8-15 parts of fly ash, 12-20 parts of zeolite, 0.6-1.5 parts of expansion agent, 0.6-2 parts of water reducer, and a total amount of water of 9-20 parts.
[0006] Furthermore, the impermeable concrete also includes the following components in parts by weight: 3-6 parts of water-based acrylic emulsion.
[0007] Furthermore, the impermeable concrete also includes the following components in parts by weight: 1-6 parts of composite fibers.
[0008] Furthermore, the specific gravity of zeolite is 2.0 and the apparent porosity is 48%.
[0009] Furthermore, the aqueous acrylic emulsion is a styrene acrylic emulsion, the solid content of the styrene acrylic emulsion is 0.31, and the glass transition temperature is 5°C.
[0010] Furthermore, the bulk density of the sand is 1580 kg / m 3, fineness modulus is 2.5-3.0. Aggregate is limestone crushed stone, with continuous grading of particle size 5-31.5, crushing value of 7.0%, and apparent density of 2500-2750kg / m 3 The specific surface area of the microspheres is 23000cm 2 / g, and the activity index is 111%.
[0011] Furthermore, the water reducing agent includes the following components in parts by weight: 9-12 parts of polycarboxylic acid mother liquor, 7-8 parts of collapse-preserving mother liquor, 2-3 parts of sodium citrate, 0.5-1 parts of plasticizing powder, 0.01-0.02 parts of alkyl sulfonate air entraining agent, 0.02-0.03 parts of polyether defoaming agent, and 78-80 parts of mixing water.
[0012] An embodiment of the present invention provides a method for preparing the above-mentioned impermeable concrete, comprising the following steps: mixing cement, microspheres, fly ash, and zeolite to obtain a first product; mixing sand and aggregate to obtain a second product; mixing mixing water with the first product to obtain a third product; mixing a water reducing agent with the third product to obtain a fourth product; and mixing the fourth product with the second product to obtain an impermeable concrete.
[0013] Further, the aqueous acrylic emulsion is mixed with mixing water and the first product.
[0014] Furthermore, the composite fiber is mixed with cement, microbeads, fly ash and zeolite.
[0015] Compared with the prior art, the present invention has the following effects:
[0016] First, the present invention adopts zeolite as a functional material. On the one hand, it serves as a thickening component to improve the self-compacting performance of the slurry; on the other hand, it also serves as a moisture carrier and is evenly dispersed in the concrete. During the concrete hardening process, moisture is released to supply water for cement hydration, prolong the secondary hydration time, and reduce the alkali content of the system to achieve the effect of self-curing, ultimately reducing shrinkage, cracking and improving strength, while also saving water resources and labor.
[0017] Secondly, the present invention introduces a low-dosage water-based acrylic emulsion, which can achieve good cement dispersion, slurry wetting and water retention effects. At the same time, the extremely fine emulsion particles can cover the surface of the newly generated cement stone during the mixing stage, thereby delaying the hydration process of the cement. During the pouring stage, the good lubrication performance can avoid the honeycomb surface caused by excessive viscosity on the contact surface with the template during concrete demoulding. During the final setting and hardening stage, the water-based acrylic emulsion can effectively delay the generation of micro cracks around the initial stage, thereby providing a certain time guarantee for the zeolite to release moisture and take effect. Finally, during the dry shrinkage and self-shrinkage stages of the concrete, the emulsion particles interspersed around the cement stone can play a buffering role, consume stress energy, and slow down the expansion of cracks.
[0018] Thirdly, the present invention increases toughness through the combined action of composite fibers, obtains the best quality and type combination through experiments on different types and quality combinations, and utilizes the synergistic effect of fibers. The use of composite fibers can significantly improve the fluidity, strength, and fold-compression ratio of concrete. At the same time, the complex fiber connection structure can consume energy during crack propagation, so that when loaded, part of the energy is consumed instead of concentrating the energy on the crack. Secondly, the tough fibers can connect to nearby cement structures to hinder crack propagation and prevent the crack from further expanding. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in combination with the scheme and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] An embodiment of the present invention provides an impermeable concrete, comprising the following components in parts by weight: 18-26 parts of cement, 7-13 parts of sand, 8-20 parts of aggregate, 5-9 parts of microspheres, 8-15 parts of fly ash, 12-20 parts of zeolite, 0.6-1.5 parts of expansion agent, 0.6-2 parts of water reducer, 9-20 parts of total water, 3-6 parts of water-based acrylic emulsion, and 1-6 parts of composite fiber.
[0021] The amount of cement used can be 18, 20, 24, 26 parts by weight, etc. Optionally, the cement is Jidong brand P.O52.5 cement.
[0022] The amount of sand can be 7, 10, 13 parts by weight. Optionally, the bulk density of the sand is 1580 kg / m 3 , fineness modulus is 2.5-3.0.
[0023] The amount of aggregate can be 8, 10, 15, 20 parts by weight. Optionally, the aggregate is limestone crushed stone with a continuous gradation of 5-31.5 particle size, a crushing value of 7.0%, and an apparent density of 2500-2750 kg / m 3 .
[0024] The amount of microbeads can be 5, 7, 9, etc. parts by weight. Optionally, the specific surface area of the microbeads is 23000 cm 2 / g, and the activity index is 111%.
[0025] The amount of fly ash used can be 8, 10, 12, 15, etc. parts by weight.
[0026] The dosage of zeolite can be 12, 15, 20 parts by weight. Optionally, the zeolite uses natural zeolite or sodium aluminosilicate with a specific uniform pore size (0.3-1nm) on the surface. The specific gravity of zeolite is 2.0, and the apparent porosity is 48%. The above zeolite has good adsorption and ion conversion functions, and obtains a viscous slurry by absorbing water in the system, which is conducive to construction and pouring. In the maintenance stage, it plays a role in internal maintenance and balancing capillary pressure through water release.
[0027] The amount of the expansion agent can be 0.6, 1, 1.2, 1.5, etc. parts by weight. Optionally, the expansion agent is sodium sulfoaluminate or potassium sulfoaluminate. The above expansion agent promotes cement hydration and accelerates the formation of ettringite, thereby offsetting the shrinkage of early coagulation.
[0028] The amount of water reducing agent can be 0.6, 1, 1.5, 2, etc. parts by weight. Optionally, the water reducing agent includes the following components by weight: 9-12 parts of polycarboxylic acid mother liquor, 7-8 parts of collapse-preserving mother liquor, 2-3 parts of sodium citrate, 0.5-1 parts of plastic powder, 0.01-0.02 parts of alkyl sulfonate air entraining agent, 0.02-0.03 parts of polyether defoamer, and 78-80 parts of mixing water.
[0029] The total amount of water used can be 9, 12, 16, 20, etc. parts by weight.
[0030] The amount of the aqueous acrylic emulsion can be 3, 5, 6 parts by weight. Optionally, the aqueous acrylic emulsion is a styrene acrylic emulsion, the solid content of the styrene acrylic emulsion is 0.31, and the glass transition temperature is 5°C. The above aqueous acrylic emulsion has medium acid value and viscosity conditions, and the ultrafine emulsion particles have highly active free groups, which themselves have hydrophilic groups such as -OH hydroxyl, -CONH2 amide or -O-ether bond, which can better produce branched cross-linking with cement hydration products under alkaline conditions, thereby improving the connection strength of the cement transition interface. At the same time, after drying, the emulsion particles can also play a role in compacting pores, buffering energy, and reducing crack generation.
[0031] The amount of the composite fiber can be 1, 3, 6, etc. parts by weight. Optionally, the composite fiber is a combination of two fibers. The composite fiber can be a combination of any two of PVA, PP, and carbon fiber.
[0032] Under the premise of meeting the requirements of strength, fluidity and slump, the composite fibers can effectively improve the stress concentration phenomenon in the vertical direction of ultra-long thin-walled concrete structures, thereby improving their toughness and crack resistance.
[0033] The present invention adopts zeolite as a functional material. On the one hand, it serves as a thickening component to improve the self-compacting performance of the slurry; on the other hand, it also serves as a moisture carrier and is evenly dispersed in the concrete. During the concrete hardening process, moisture is released to supply water for cement hydration, prolong the secondary hydration time, and reduce the alkali content of the system to achieve the effect of self-curing, ultimately reducing the purpose of shrinkage, cracking and improving strength, while also saving water resources and labor.
[0034] The invention introduces a low-dosage water-based acrylic emulsion, which can achieve good cement dispersion, slurry wetting and water retention effects. At the same time, extremely fine emulsion particles can cover the surface of newly generated cement stone in the stirring stage to delay the hydration process of cement. In the pouring stage, good lubrication performance can avoid honeycomb roughness generated on the surface in contact with the template due to excessive viscosity when the concrete is demoulded. In the final setting and hardening stage, the water-based acrylic emulsion can effectively delay the generation of micro cracks around the initial stage, providing a certain time guarantee for the zeolite to release water and produce an effect. Finally, in the dry shrinkage and self-shrinkage stages of the concrete, the emulsion particles interspersed around the cement stone can play a buffering role, consume stress energy, and slow down the expansion of cracks.
[0035] The present invention achieves toughness enhancement through the combined action of composite fibers, obtains the best quality and type combination through experiments on different types and quality combinations, and utilizes the synergistic effect of fibers. The use of composite fibers can significantly improve the fluidity, strength, and fold-compression ratio of concrete. At the same time, the complex fiber connection structure can consume energy during crack propagation, so that when loaded, part of the energy is consumed instead of concentrating the energy on the crack. Secondly, the tough fibers can connect to nearby cement structures to hinder crack propagation and prevent the crack from further expanding.
[0036] An embodiment of the present invention provides a method for preparing the above-mentioned impermeable concrete, comprising the following steps:
[0037] (1) Cement, microspheres, fly ash and zeolite are mixed to obtain a first product.
[0038] In the above steps, the composite fiber is mixed with cement, micro beads, fly ash and zeolite.
[0039] (2) Mixing sand and aggregate to obtain a second product.
[0040] (3) Mixing the mixing water with the first product to obtain a third product.
[0041] In the above steps, the aqueous acrylic emulsion is mixed with the mixing water and the first product. The aqueous acrylic emulsion is first mixed with the mixing water, and then the mixture is mixed with the first product.
[0042] (4) Mixing the water reducing agent with the third product to obtain a fourth product.
[0043] (5) The fourth product is mixed with the second product to obtain an impermeable concrete.
[0044] The present invention can significantly improve the self-compacting property of concrete while meeting the strength requirements and has both self-curing properties, can effectively reduce cracking of concrete structures, enhance the concrete's own anti-seepage properties, and improve the building's self-waterproofing properties, which not only saves engineering investment but also simplifies the construction process.
[0045] The following is a detailed description with reference to specific embodiments:
[0046] The cement is Jidong brand P.O52.5 cement;
[0047] The zeolite is obtained by crushing analcime, with a specific gravity of 2.0 and an apparent porosity of 48%;
[0048] The bulk density of sand is 1580kg / m 3 , fineness modulus is 2.5-3.0;
[0049] The aggregate is limestone crushed stone with a continuous grading of particle size 5-31.5, a crushing value of 7.0%, and an apparent density of 2500-2750kg / m 3 ;
[0050] The water-based acrylic emulsion is a styrene acrylic emulsion, the solid content of the styrene acrylic emulsion is 0.31, the glass transition temperature is 5°C, and it is a white turbid liquid;
[0051] The specific surface area of the microspheres is 23000cm 2 / g, and the activity index is 111%.
[0052] The expansion agent is sodium sulphoaluminate.
[0053] Example 1
[0054] (1) According to weight, 25 parts of cement, 8 parts of microspheres, 12 parts of fly ash, 15 parts of natural zeolite, 0.6 parts of expansion agent and 2.3 parts of composite fiber (PVA: carbon fiber = 5:5) were unloaded from a raw material bin into a bucket car and transported to a stirring tank for mixing and stirring for 45 seconds to obtain a first product.
[0055] (2) According to weight, 8 parts of sand and 9 parts of aggregate are discharged into a mixing bin for mixing and standby use to obtain a second product.
[0056] (3) According to the weight ratio, 9 parts of polycarboxylic acid mother solution, 8 parts of collapse-preventing mother solution, 3 parts of sodium citrate, 0.5 parts of plastic-preserving powder, 0.02 parts of alkyl sulfonate air-entraining agent and 0.03 parts of polyether defoaming agent are weighed and mixed with 80 parts of mixing water, and the mixture is stirred evenly to obtain a water reducing agent for later use.
[0057] (4) Open the resin tank, draw 4 parts of water-based acrylic emulsion by weight into the water tank 1, add 6 parts of mixing water to dilute evenly, and then uniformly inject into the stirring kettle and start stirring at 120 r / min. After the water in the water tank 1 is drained, add 2.4 parts of mixing water to wash the tank wall, and then continue to put it into the stirring kettle for mixing and stirring. The stirring time of the stirring kettle is 100 s to obtain the third product.
[0058] (5) Inject 1.5 parts of water reducing agent into the second water adding tank by weight, mix well and inject into the stirring tank and stir for 30 seconds. During the stirring period, pour the second product into it, stir at a constant speed of 120 r / min for 45 seconds, and then stir at a high speed of 240 r / min for 105 seconds to obtain concrete.
[0059] Example 2
[0060] (1) According to weight, 22 parts of cement, 6 parts of microspheres, 13 parts of fly ash, 20 parts of natural zeolite, 1 part of expansion agent and 2 parts of composite fiber (PVA:PP=8:2) were unloaded from a raw material bin into a bucket car and transported to a stirring tank for mixing and stirring for 30 seconds to obtain a first product.
[0061] (2) According to weight, 10 parts of sand and 11 parts of aggregate are discharged into a mixing bin for mixing and standby use to obtain a second product.
[0062] (3) According to weight, 12 parts of polycarboxylic acid mother solution, 7 parts of collapse-preserving mother solution, 2 parts of sodium citrate, 1 part of plastic-preserving powder, 0.01 parts of alkyl sulfonate air entraining agent, 0.02 parts of polyether defoaming agent and 78 parts of mixing water are weighed and stirred evenly to obtain a water reducing agent for later use.
[0063] (4) Open the resin tank, draw 6 parts of water-based acrylic emulsion by weight into the water tank 1, add 5 parts of mixing water to dilute evenly, and then uniformly inject into the stirring kettle and start stirring at 120 r / min. After the water in the water tank 1 is drained, add 3 parts of mixing water to wash the tank wall, and then continue to put it into the stirring kettle for mixing and stirring. The stirring time of the stirring kettle is 90 s to obtain the third product.
[0064] (5) Inject 2 parts of water reducing agent into the second water adding tank by weight, mix well and inject into the stirring tank and stir for 25 seconds. During the stirring period, pour the second product into it, stir at a constant speed of 120 r / min for 60 seconds, and then stir at a high speed of 240 r / min for 105 seconds to obtain concrete.
[0065] Example 3
[0066] (1) According to weight, 25 parts of cement, 5 parts of microspheres, 15 parts of fly ash, 12 parts of natural zeolite, 1.5 parts of expansion agent and 2 parts of composite fiber (PVA:PP=8:2) were unloaded from a raw material bin into a bucket car and transported to a stirring tank for mixing and stirring for 30 seconds to obtain a first product.
[0067] (2) According to weight, 9 parts of sand and 14 parts of aggregate are discharged into a mixing bin for mixing and standby use to obtain a second product.
[0068] (3) According to the weight ratio, 10 parts of polycarboxylic acid mother solution, 8 parts of collapse-preserving mother solution, 2 parts of sodium citrate, 1 part of plastic-preserving powder, 0.02 parts of alkyl sulfonate air entraining agent, 0.03 parts of polyether defoaming agent and 79 parts of mixing water are weighed and stirred evenly to obtain a water reducing agent component for later use.
[0069] (4) Open the resin tank, draw 6 parts of water-based acrylic emulsion by weight into the water tank 1, add 10 parts of mixing water to dilute evenly, and then uniformly inject into the stirring kettle and start stirring at 120 r / min. After the water in the water tank 1 is drained, add 4.2 parts of mixing water to wash the tank wall, and then continue to put it into the stirring kettle for mixing and stirring. The stirring time of the stirring kettle is 90 s to obtain the third product.
[0070] (5) Inject 2 parts of water reducing agent into the second water adding tank by weight, mix well and inject into the stirring tank and stir for 25 seconds. During the stirring period, pour the second product into it, stir at a constant speed of 120 r / min for 60 seconds, and then stir at a high speed of 240 r / min for 105 seconds to obtain concrete.
[0071] Test Example 1
[0072] Referring to the national standard GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the compressive strength test and U-shaped instrument height test were carried out on the concrete of Examples 1-3; referring to the national standard GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the water seepage height method was used to carry out water permeability resistance tests on the concrete of Examples 1-3. The test results are shown in Table 1.
[0073] Table 1 Performance test results of concrete in the embodiment
[0074]
[0075]
[0076] By comparing the data of Examples 1-3 and conventional pipe gallery concrete, it can be seen that the concrete of Examples 1-3 has good physical properties at all ages; at the same time, through the U-type instrument concrete flow rise height test, it can be seen that the concrete of Examples 1-3 can reach more than 320mm both initially and after 3h, indicating excellent self-compactness; after improvement by adding composite fiber and styrene-acrylic emulsion, the concrete's water seepage resistance and shrinkage value are significantly reduced.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An impermeable concrete, characterized in that: The composition comprises the following components in parts by weight: 18-26 parts of cement, 7-13 parts of sand, 8-20 parts of aggregate, 5-9 parts of microspheres, 8-15 parts of fly ash, 12-20 parts of zeolite, 0.6-1.5 parts of expansion agent, 0.6-2 parts of water reducer, and the total water volume is 9-20 parts.
2. The impermeable concrete according to claim 1, characterized in that: It also includes the following components in parts by weight: 3-6 parts of water-based acrylic emulsion.
3. The impermeable concrete according to claim 1, characterized in that: It also includes the following components in parts by weight: 1-6 parts of composite fiber.
4. The impermeable concrete according to claim 1, characterized in that: The zeolite has a specific gravity of 2.0 and an apparent porosity of 48%.
5. The impermeable concrete according to claim 2, characterized in that: The aqueous acrylic emulsion is a styrene acrylic emulsion, the solid content of the styrene acrylic emulsion is 0.31, and the glass transition temperature is 5°C.
6. The impermeable concrete according to claim 1, characterized in that: The bulk density of the sand material is 1580kg / m 3 , fineness modulus is 2.5-3.0; The aggregate is limestone crushed stone with a continuous gradation of particle size of 5-31.5, a crushing value of 7.0%, and an apparent density of 2500-2750 kg / m 3 ; The specific surface area of the microspheres is 23000 cm 2 / g, and the activity index is 111%.
7. The impermeable concrete according to claim 1, characterized in that: The water reducing agent comprises the following components by weight: 9-12 parts of polycarboxylic acid mother liquor, 7-8 parts of collapse-preserving mother liquor, 2-3 parts of sodium citrate, 0.5-1 parts of plastic-preserving powder, 0.01-0.02 parts of alkyl sulfonate air-entraining agent, 0.02-0.03 parts of polyether defoaming agent, and 78-80 parts of mixing water.
8. A method for preparing the impermeable concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing cement, microspheres, fly ash, and zeolite to obtain a first product; mixing sand and aggregate to obtain a second product; mixing mixing water with the first product to obtain a third product; mixing a water reducing agent with the third product to obtain a fourth product; The fourth product is mixed with the second product to obtain impermeable concrete.
9. The preparation method according to claim 8, characterized in that: The aqueous acrylic emulsion is mixed with the mixing water and the first product.
10. The preparation method according to claim 8, characterized in that: The composite fiber is mixed with the cement, the microspheres, the fly ash and the zeolite.